answersLogoWhite

0


Best Answer

By rearranging and combining similar terms. For example, 3x + 5x = (3+5)x = 8x.

User Avatar

Wiki User

โˆ™ 2010-08-21 13:30:21
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
844 Reviews

Add your answer:

Earn +20 pts
Q: How do you simplfy 3x plus 2y plus 5x plus y?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

2y plus 5x 13 2y and ndash 3x 5?

If you mean: 2y+5x = 13 and 2y-3x = 5 then x = 1 and y = 4


What is the answer for -3x-2x plus 4y-2y?

In its simplest form: 2y -5x


What are the exact values of x and y when 3x plus 2y equals 5x plus 2y equals 7?

If: 3x+2y = 5x+2y = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtract the 1st equation from the 2nd equation: 2x = 0 or x = o By substitution: x = 0 and y = 3.5


What are the solutions to the simultaneous equation of 3x plus 2y equals 5x plus 2y equals 14 showing work?

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7


What is 5x - 3y -7x plus 2y plus 3x?

5x - 3y -7x + 2y +3x = (5-7+3)x + (-3+2)y = x - y


What are the values of x and y in the equation 3x plus 2y equals 5x plus 2y equals 7 show work?

If: 3x+2y = 5x+2y = 7 which is the same as 7 = 7 = 7 Then: 3x+2y = 7 and 5x+2y = 7 Subtracting equations: x = 0 Therefore by substitution: x = 0 and y = 3.5


How do you simplify -5(x plus 2y)-3x plus 8y plus 5?

-5(x + 2y) -3x + 8y + 5 = -5x -10y -3x + 8y + 5 = -8x -2y + 5


3x plus 2y multiplied by 5x-3y equals?

(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2


3x plus 2y equals 20 and 5x-2y equals 1?

3x+2y=20 5x-2y=1 (3x+2y) + (5x-2y)= 20+1 3x+5x= 21....... 8x=21.........x=2 5/8 Subsitute x=3(2 5/8)+ 2y=20........... 7 7/8 +2y=20.........2y= 20- 7 7/8....... y=6 1/16


How do you solve for 5x plus y equals 1 and 3x plus 2y equals 2?

For 5x+y=1, you would subtract 5x from each side, so you would get y=1-5x For 3x+2y=2, you would subtract 3x from each side, and then divide by 2. 2y=2-3x y=1-(3/2)x


Add 3x 2y-5x?

-2x+2y


5x-2y plus 3z-2x-y-4z equals?

5x-2y+3z-2x-y-4z=3x-3y-z

People also asked